Analisa Terhadap Konsep Nafkah Terhadap Ketahanan Pangan Keluarga Islam Atas Wabah Covid-19 Di Kelurahan Tinalan Kota Kediri (Ditinjau Dari Maqashidi Syariah Perspektif Al-Syatibi) - Nurmahmudah; Dicky Aris Setiawan (Institut Agama Islam Negeri (IAIN) Kediri, 2021)
The world is in a significant economic crisis in various countries caused by the emergence of the 2019-nCoV(Novel Coronavirus).This pandemic not only attacking human lives also caused a crisis in the country’seconomy.This can be seen significantly in household life, especially in Tinalan Village which in fact is positivelyaffected by corona.The government’s regulation on the handling of the 2019-nCoV is the implementation ofthe PSBB (Large-Scale Social Restrictions), directly demands that all community activities be recommended tobe implemented in the home.Thus, with the emergence of the 2019-nCoV is hampering the regional economyas well as the household economy, one of them is household food security.This is factored by monthly income,family members, and monthly expenses in one house.This study will examine how the concept of living onfood security of Islamic families sees the phenomenon of the Covid-19, specifically by the Islamic family ofTinalan Village, Kediri city by reviewing from the sharia maqashidi al-Syatibi perspective. A total of 160respondents were selected as research samples in March to May 2020 to be reviewed according to the contextof the study. The people of Tinalan Village understand this situation, so they adapt to the governance of theirhousehold spending expenditures.This is in accordance with the principles of marriage prescribed by Islamand reaffirmed in al-Syatibi’s maqashidi shari’ah.